Effects of Rear Angle on the Turbulent Wake Flow between Two in-Line Ahmed Bodies - Ebenezer Essel; Subhadip Das; Ram Balachandar (Atmosphere, 2020)
Understanding the wake characteristics between two in-line vehicles is essential for improving and developing new strategies for reducing in-cabin air pollution. In this study, Ahmed bodies are used to investigate the effects of the rear slant angle of a leading vehicle on the mean flow and turbulent statistics between two vehicles. The experiments were conducted with a particle image velocimetry at a fixed Reynolds number, <semantics> R e H = 1.7 × 10 4 </semantics> , and inter-vehicle spacing distance of <semantics> 0.75 L </semantics> , where <semantics> H </semantics> and <semantics> L </semantics> are the height and length of the model. The rear slant angles investigated were a reference square back, high-drag angle ( <semantics> α = 25 ° </semantics> ) and low-drag angle ( <semantics> α = 35 ° </semantics> ). The mean velocities, Reynolds stresses, production of turbulent kinetic energy and instantaneous swirling strength are used to provide physical insight into the wake dynamics between the two bodies. The results indicate that the recirculation region behind the square back Ahmed body increases while those behind the slant rear-end bodies decreases in the presence of a follower. For the square back models, the dominant motion in the wake region is a strong upwash of jet-like flow away from the road but increasing the rear slant angle induces a stronger downwash flow that suppresses the upwash and dominates the wake region.